Conexões entre a moda atemporal e o consumo consciente na construção da marca Tezzo - Pasqualini, Jéssica Perazzo Ferreira (Universidade do Vale do Rio dos Sinos, 2021)
This work addresses the theme of fashion's timelessness. The objective of this research is to develop a timeless women's fashion brand, offering quality fashion, with a cause and without a defined season, enabling the expression of individuality outside mass consumption. For this it was necessary to gather information and study the history of fashion until reaching mass consumption in the digital age that ended up transforming the social role of fashion into a commercial and ephemeral role. And how such factors drove consumers to look for products with greater differentiation, timelessness, and sustainability. Still, the study proposes to answer this problem: How is it possible to create a timeless brand proposal, leaving mass consumption, delivering fashion that tells a story, considering the preservation of time and being a source of consumption with cause? The general objective of this work is to develop a timeless women's fashion collection, aimed at the conscious consumption segment, offering quality fashion without a defined season, enabling the expression of individuality.
Keywords: Consumismo; Moda com causa; Moda atemporal; Sustentabilidade; Consumerism; Fashion with cause; Timeless fashion; Sustainability